Types of Syntactic Units Encountered in Deixis - Norova Bakhriniso Yuldashevna (Genius Journals, 2022)
From the point of view of traditional linguistics, any sentence, regardless of its language, consists of primary and secondary parts of speech. The theory of secondary fragments is one of the most recent units of linguistics. We know that the usual classification of secondary parts consists of complement, determiner, and case.
Keywords: small syntax; sentence syntax; a large syntax; or a text syntax